Non-symbiotic N2 fixation is less sensitive to changes in temperature than carbon mineralization in Northern forest soils - Eduardo Vázquez; Marie Spohn (Geoderma)
Northern forests are characterized by low temperatures that play a key role in the whole ecosystem functioning. However, Northern forests are expected to experience the largest temperature increase of all forest biomes in the next decades, which could affect central ecosystem processes, such as carbon (C) mineralization and N2 fixation. Aiming to clarify the temperature-dependence of non-symbiotic N2 fixation and C mineralization in Northern forest soils, we quantified the rates of both processes in soils of Scots Pine (Pinus sylvestris) forests located along a temperature gradient in Sweden in laboratory incubations at different temperatures (5, 12 and 20 °C). Our results show that N2 fixation by free-living bacteria in the organic layer of these forest soils ranges between 2 and 10 kg N ha−1 yr−1 which highlights the importance of non-symbiotic N2 fixation in Northern forest soils. We found a positive correlation between non-symbiotic N2 fixation per area and mean annual temperature (MAT). This relationship was caused by the positive relationship between the organic layer stock and MAT rather than by the direct effect of temperature on the process rate. In contrast, C mineralization per g of soil was negatively related to MAT. Furthermore, our results show that C mineralization is more sensitive to changes in incubation temperature (it increased by a factor of 2.2 from 5 to 12 °C as well as from 12 to 20 °C) than non-symbiotic N2 fixation that was not significantly affected by incubation temperature. Taken together, while N2 fixation responded little to changes in incubation temperature, our results suggest that the higher N2 fixation rate per area at sites with higher MAT is beneficial for primary production and organic matter inputs to soil leading to larger organic layer stocks. Hence, there is a positive, temperature-dependent feedback among non-symbiotic N2 fixation, primary production, and the organic layer formation in Northern forests.